Clinical manifestations and treatment outcomes among hospitalised COVID-19 patients in tertiary hospitals in Tanzania, 2021-2022: a retrospective cohort study - Abel Makubi; Candida Moshiro; Elisha Fred Otieno Osati; Grace Ambrose Shayo; Raphael Z Sangeda; Tumaini Joseph Nagu; Naveeda Adams; Athumani Ramadhani; Bahati Wajanga; Albert Muniko; Jeremiah Seni; Mary A Nicholaus; et al. (BMJ Publishing Group, 2024)
Background There have been differential mortality rates from COVID-19 in different parts of the world. It is not clear whether the clinical presentation does also differ, thus the need for this study in a sub-Saharan African setting. The aim of this study was to describe the clinical manifestations and outcomes of patients diagnosed with COVID-19 in selected tertiary hospitals in Tanzania.Methods This was a retrospective analysis of hospitalised adults confirmed SAR-COV-2 infection in five tertiary-level hospitals in Tanzania. Data collected and analysed included sociodemographic, radiological and clinical characteristics of the patients as well as the outcome of the admission (discharge vs death).Results Out of 1387 COVID-19 patients, 52% were males. The median age was 60 years ((IQR)=(19-102)). The most common symptoms were dyspnoea (943,68%), cough (889, 64%), fever (597,43%) and fatigue (570, 41%). In-hospital mortality was (476, 34%). Mortality significantly increased with increasing age, being the most in age >90 years (aHR (95% CI)=4.4 (2.52 to 28.82), p=0.02). Other predictors of mortality were not possessing a health insurance, (aHR (95% CI)=3.7 (1.09 to 14.25), p=0.04); chest pain, (aHR (95% CI)=2.27 (1.36 to 4.13), p=0.03); HIV positivity, (aHR (95% CI)=3.9 (1.46 to 8.15), p=0.03); neutrophilia, (aHR (95% CI)=1.12 (1.01 to 2.65), p=0.03); no use of ivermectin, (aHR (95% CI)=1.21 (1.04 to 1.57), p=0.04) and non-use of steroids, (aHR (95% CI)=1.36 (1.18 to 2.78), p=0.04). The retrospective nature of this study which based on documented patients' records, with a large number of patients left out of the analysis due to missed data, this might in a way affect the results of the present study.Conclusion In-hospital mortality was 34%. The independent predictors of mortality were advanced age, HIV infection, no possession of a health insurance, chest pain, neutrophilia and no use of steroids or ivermectin.